Fiqh Learning Implementation Fosters Student Prayer Discipline in Modern Islamic Schools: Implementasi Pembelajaran Fikih Menumbuhkan Kedisiplinan Shalat Siswa di Sekolah Islam Modern - Najwa Ammara Jauza; Sokon Saragih (Pedagogia : Jurnal Pendidikan, 2026)
General Background Educational systems face critical challenges in balancing cognitive knowledge acquisition with spiritual character formation among adolescents. Specific Background Within religious institutions, declining moral values necessitate comprehensive jurisprudence instruction to establish fundamental worship practices, particularly regarding obligatory congregational routines. Knowledge Gap While previous literature heavily emphasizes theoretical instruction, limited research explores the holistic integration of direct practice, continuous teacher modeling, and structural habituation within boarding ecosystems. Aims This qualitative case study describes the pedagogical strategies used to build the quality of adolescent worship performance at MTs Ta’dib Al-Mu’allimin Al-Islamiy. Results Observations and interviews reveal that combining systematic material delivery, direct movement demonstrations, and educator role-modeling successfully cultivates worship consistency and movement accuracy. Furthermore, structured reward and punishment systems, alongside parental supervision, positively shape daily religious routines, although limited ablution infrastructure and fluctuating learner motivation present significant barriers. Novelty This research conceptualizes religious education not merely as theoretical knowledge transfer but as an integrated ecosystem requiring both structural regulations and continuous practical modeling. Implications Educational institutions must upgrade infrastructure, such as constructing circular ablution fountains to save time, and adopt digital tracking applications to support holistic spiritual development. Highlights Direct movement demonstrations and continuous educator role-modeling cultivate worship consistency and accuracy. Structured reward frameworks and parental involvement positively shape daily religious routines. Infrastructure limitations regarding ablution facilities create significant barriers to congregational worship efficiency. Keywords Religious Instruction; Congregational Worship; Spiritual Character; Teacher Modeling; Worship Habituation